Control de inventarios (medicamentos) en el área de Administración – Bodega en el Distrito de Salud 12D05 Palenque – Vinces en el periodo 2020 - Mora Sovenis, Tais Yamileth (2021)
The inventories integrate control procedures which are carried out in different functions that help to transmit experiences and knowledge when making decisions, in this investigation the problems that are triggered in the Administration area - Warehouse of the Health District 12D05 are shown, a public entity located in the Vinces canton, Los Ríos province. The research to be dealt with within this entity is based on showing the shortcomings that exist in the control of supplies (medicines) which do not show complete information since the system used is the Excel program where through the Kardex cards they carry the records of existence, incomes and outflows of the products, however this record does not show the expiration date of some of the supplies, which can lead to unwanted inventory losses or drops, because it does not show an alert system that helps to know in advance the products that are about to expire. Among the results of this research, the key points where the entity's problem is centered are exposed, making known clearly and specifically and with an easy reading put to any interpretation, which will allow the entity to make decisions in advance to avoid results that may affect its operation.